A prevalent variant in PPP1R3A impairs glycogen synthesis and reduces muscle glycogen content in humans and mice. - Savage, D; Zhai, L; Ravikumar, B; Choi, C; Snaar, J; McGuire, A; Wou, SE; Medina-Gomez, G; Kim, S; Bock, C; Segvich, D; Solanky, B; et al. (Public Library of Science, 2008)
BACKGROUND: Stored glycogen is an important source of energy for skeletal muscle. Human genetic disorders primarily affecting skeletal muscle glycogen turnover are well-recognised, but rare. We previously reported that a frameshift/premature stop mutation in PPP1R3A, the gene encoding RGL, a key regulator of muscle glycogen metabolism, was present in 1.36% of participants from a population of white individuals in the UK. However, the functional implications of the mutation were not known. The objective of this study was to characterise the molecular and physiological consequences of this genetic variant. METHODS AND FINDINGS: In this study we found a similar prevalence of the variant in an independent UK white population of 744 participants (1.46%) and, using in vivo (13)C magnetic resonance spectroscopy studies, demonstrate that human carriers (n = 6) of the variant have low basal (65% lower, p = 0.002) and postprandial muscle glycogen levels. Mice engineered to express the equivalent mutation had similarly decreased muscle glycogen levels (40% lower in heterozygous knock-in mice, p < 0.05). In muscle tissue from these mice, failure of the truncated mutant to bind glycogen and colocalize with glycogen synthase (GS) decreased GS and increased glycogen phosphorylase activity states, which account for the decreased glycogen content. CONCLUSIONS: Thus, PPP1R3A C1984DeltaAG (stop codon 668) is, to our knowledge, the first prevalent mutation described that directly impairs glycogen synthesis and decreases glycogen levels in human skeletal muscle. The fact that it is present in approximately 1 in 70 UK whites increases the potential biomedical relevance of these observations.